THE ROLE OF INVESTMENT AND MODERNIZATION IN THE DEVELOPMENT OF THE UZBEK ECONOMY (ResearchJet Journal of Analysis and Inventions, 2021)
This article provides an analysis of the role of investment and modernization in the economy, its importance. The level of development of any country, that is, the development and growth of the economy, largely depends on the investment process in the country. Technical and economic modernization and, if necessary, radical renewal of the economy, development of priority sectors of the economy, increasing the number of competitive goods and services that meet the requirements of a market economy, ie meeting the requirements of foreign and domestic markets and creating new ones. is one of the functions.